A Diagnostic Pattern in Guillain-Barré Syndrome (GBS) in Children a Multi-Center Study - Main Ayaz Ul Haq, Main Iftikar Ul Haq, Fawad Ali, Mehtab Alam, Zia Ullah Qazi, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: Analyze how children with GBS manage in the clinic. Materials and methods: From 2015 to 2020, researchers at the Department of Neurosurgery at LRH and HMC Hospital peshawar analyzed data from 67 children (younger than 14) hospitalized at the hospitals with AFP. the Multicenter study in All patients had standard examinations, with most also undergoing [CSF examination], nerve conduction studies (NCS), and electromyography (EMG), depending on available resources. Supportive care, intravenous immunoglobulin (IVIG), and plasmapheresis were employed as treatment options, with the choice of modality determined by clinical need and accessibility to the respective procedures. Results: Sixty-nine percent (60) of the AFP cases were determined to be GBS. The average kid with GBS was six years old, and the male-to-female ratio was 1.06 to 1. Sixty-eight percent of patients had a previous medical history, seventy-two percent had sensory complaints, and sixty-two percent had autonomic dysfunction. There were ninety-three percent of patients with classical GBS (symmetrical ascending paralysis), two percent with descending paralysis, four percent with relapsing variation, and one with chronic inflammatory demyelinating polyneuropathy. A third of patients had the demyelinating type, another third had demyelinating with axonal involvement, and another twenty-one percent were classed as unclassified based on their electrophysiological investigations. Mechanical ventilation was necessary for 28 patients (44%). Mechanical breathing was necessary for 36% of those with axonal type and 24% with demyelinating type. Of the 28 patients given IVIG, 18 exhibited improvement, five did not, and plasmapheresis was performed on them. Conclusion: The majority of cases of AFP can be attributed to exposure to GBS. IVIG is an effective therapeutic strategy for children with GBS, and GBS with axonal involvement is more severe than demyelinating kind. Keywords: Children with Acute Flaccid Paralysis, Guillain-Barre Syndrome